Stolen Asset Recovery - An End to Public Fund Mismanagement by PEPs: Applicability of Learned Lessons to Sri Lankan Context - Ranasinghe, R.S.L.B. (Faculty of Commerce and Management Studies, University of Kelaniya Sri Lanka, 2022)
Allegations into corruption and public fund mismanagement, and consequentially, money laundering, have reportedly increased at a rapid rate in Sri Lanka. The country predominantly relies on Conviction-Based procedures to curtail such cases. While a rudimentary legal framework is in place, the case success rate for Politically Exposed Persons (PEPs) has been discouraging. UNODC and UNCAC-backed Stolen Asset Recovery (StAR) initiative provides for Non-Conviction Based (NCB) Confiscation, which was initially recommended for local implementation. The study aims to explore and assess the applicability of the Non-Conviction Based confiscation procedure as a legal remedy. A qualitative single case study method is used, and the case analysis is conducted under the holistic approach. The case study selected is from a country that relies on a similar English Law driven common law system for criminal prosecution. Legal applications made in the selected country to foster NCB, can be provisionally applied in the local context due to similarity in the existing framework. Holistic analysis into legal, political, social, and economic impact reveals possible consequences that can be expected in Sri Lanka post-application. The study ensures that the SDG 16 is achieved as far as the specific targets of Substantially reducing corruption and bribery and Developing effective, accountable, and transparent institutions are concerned. The study sets the framework and identifies potential barriers to implementing NCB to address legal and social barriers and to accomplish the universally compatible application.
Keywords: Corruption, Non-Conviction Based Confiscation, Public Fund Mismanagement, SDG 16, Stolen Asset Recovery